The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.4093/dmj.2015.39.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Thyroid Dysfunction in Patients with Metabolic Syndrome and Its Relationship with Components of Metabolic Syndrome

Abstract: BackgroundThyroid dysfunction (TD) and metabolic syndrome (MetS) are known risk factors for atherosclerotic cardiovascular disease (ASCVD). TD is risk factor for ASCVD mediated by the effects of thyroid hormones on lipid metabolism and blood pressure hence the components of MetS. It is possible that coexistence of these two disease entities and unrecognized TD in patients with MetS might substantially increase ASCVD risk. Moreover, little is known about the relationship between TD and the components of MetS. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
42
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 27 publications
7
42
3
1
Order By: Relevance
“…These finding were similar to those obtained in the studies on Hispanic population by Garcia GJ et al, Nepal population Gyawali P et al, and Chennai population by Shantha GP et al 10,12,13 Serum triglycerides and TG/HDL-C ratio, which are surrogate markers for insulin resistance, were significantly elevated in study group compared to control group. This indicates that the study group may have greater insulin resistance than the control group.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…These finding were similar to those obtained in the studies on Hispanic population by Garcia GJ et al, Nepal population Gyawali P et al, and Chennai population by Shantha GP et al 10,12,13 Serum triglycerides and TG/HDL-C ratio, which are surrogate markers for insulin resistance, were significantly elevated in study group compared to control group. This indicates that the study group may have greater insulin resistance than the control group.…”
Section: Discussionsupporting
confidence: 80%
“…Another study from Nepal showed that the prevalence of TD in patients with MetS was 31.84% and its pattern showed high prevalence of SCH (29.32%) followed by hypothyroidism (1.67%) and subclinical hyperthyroidism (0.83%). 12 . In this study, the mean BMI, waist circumference, waist/hip ratio, systolic and diastolic blood pressure, fasting blood glucose, triglycerides, were significantly higher and HDL-C levels were significantly lower in the study group (P<0.001) than in the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lately, there has been increased interest in the effects of IR and MS on the thyroid (1-3). The association of IR and MS with thyroid diseases has been reported by several studies that have shown an increased incidence of hypothyroidism, autoimmune thyroiditis, thyroid nodules, and differentiated thyroid carcinomas along with other systemic malignancies (4,5). Patients with both POS and IR have been described as having an increased frequency of thyroid disorders such as hypothyroidism, Hashimoto's thyroiditis, and Graves' disease (6).…”
Section: Introductionmentioning
confidence: 99%
“…Altered serum thyroid-stimulating hormones (TSHs) levels with normal or altered thyroid hormone, free triiodothyronine (FT3) and free thyroxine (FT4) is defined as thyroid dysfunction [2]. Different TDs include Hashimoto's thyroiditis, hyperthyroidism, and hypothyroidism [3].…”
Section: Introductionmentioning
confidence: 99%